INTERNET GOVERNANCE FOR WHOM? CIVIL SOCIETY, REPRESENTATION, AND DIGITAL RIGHTS - Grover, Rohan (AoIR Selected Papers of Internet Research, 2021)
Internet governance institutions embrace a multistakeholder approach, which calls for civil society organizations (CSOs) to represent community interests. How well do digital rights CSOs fulfill these expectations of “community representation”? Through a case study of the Internet Freedom Foundation, an Indian digital rights organization, this paper evaluates community engagement mechanisms through the lens of equity and democratization, and identifies a gap between expectations and observed practices. It concludes that evaluating representation in digital-native CSOs should account for both socioeconomic and technological dynamics in both transnational and national contexts. This paper offers a contribution to an emergent understanding of civil society’s role in internet governance, grounded in a postcolonial critique of representation and legitimacy, in order to understand whose voices are heard, and whose are still excluded, from internet governance processes.